2010
DOI: 10.1007/s11340-009-9311-0
|View full text |Cite
|
Sign up to set email alerts
|

“Equivalent” Electromechanical Coefficient for IPMC Actuator Design Based on Equivalent Bimorph Beam Theory

Abstract: This paper addresses an "equivalent" electromechanical coupling coefficient that may be used in designing Ionic Polymer Metal Composite (IPMC) actuators. The coefficient is not a material constant and derived from equivalent bimorph beam model. The collective effect of the membrane thickness and operating voltage on the coefficient is demonstrated by using a design of experiment (DOE) of three and five levels of the two factors, respectively. Experiments and linear finite element analyses with MD.NASTRAN at DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Further, increase in frequency drives to the critical point C, beyond which the system again exhibits stable condition. It is further observed that, frequency beyond point C, the amplitude decreases to point D. This observation is consistent with the results presented by [5,31]. If the system is driven by a voltage with frequency in between point X and C the response will be thus unstable and may results in failure in this range.…”
Section: Numerical Resultssupporting
confidence: 91%
“…Further, increase in frequency drives to the critical point C, beyond which the system again exhibits stable condition. It is further observed that, frequency beyond point C, the amplitude decreases to point D. This observation is consistent with the results presented by [5,31]. If the system is driven by a voltage with frequency in between point X and C the response will be thus unstable and may results in failure in this range.…”
Section: Numerical Resultssupporting
confidence: 91%
“…Because of the helical structure of the IPMC actuator, the helical bimorph beam model is newly developed for obtaining the electromechanical coupling coefficient, which can be considered as equivalent material parameter for the finiteelement analyses [47], [48]. The geometry of the proposed helical IPMC actuator is simply modeled by using the 3-D modeling software package.…”
Section: Modeling With a Commercial Fe Packagementioning
confidence: 99%
“…Cilingir et al 37 used design of experiments (DOE) to demonstrate the effect of thickness and operating voltage on the coefficient which are also main factors for maximum tip displacement. They also stated that the curvature of the IPMC strip before excitation is one of the factors for "equivalent" coupling coefficient.…”
Section: Characteristics Of Ipmc Under the Variation Of Thicknessmentioning
confidence: 99%
“…The advantage of their approach is that although the IPMC actuation is a transport phenomenon, it is treated as response by piezoelectric materials which are easier to model in commercial finite element analysis software. 37 …”
Section: Numerical Modeling Of Ipmcmentioning
confidence: 99%